Convergência entre telefonia fixa e móvel no Brasil: modelagem mercadologócia e sustentabilidade estratégica - Duschitz, Fernando da Costa (2006)
The convergence of services typically provided by fixed telecommunication companies and those provided by mobile companies is a phenomenon that has happened worldwide for over ten years. Understood as an evolutionary phenomenon, the convergence between fixed and mobile operators would have three main drivers: the development of technology itself, based for instance in the digitalization of telecommunications; the merging of a marketoriented view, motivated by high competition levels, with the search for technological innovations; or the simple junction of financial assets from different industries, aiming towards a more efficient allocation of financial resources. Worldwide there are many known convergent telecommunication services, while in Brazil convergence may be seen as embrionary. Considering the relevant amount of incomes occurred from both fixed and mobile markets in Brazil and the high level of competition in the Country, the study and application of solutions for convergence may generate real competitive advantages. Therefore, the purpose of this study is to evaluate the main Brazilian telecommunication companies, as well as the resources or services they deploy to achieve convergence, using the VRIO framework methodology developed by Barney, which is based on the Resource Based View theory (RBV)